Problems and development prospects of poultry farming in Ukraine - Vinichenko, Ihor; Makhovsky, Dmitry (Technology audit and production reserves, 2015)
The article stipulates that the modern poultry farming in Ukraine is the most dynamic sector of productive livestock and able to produce in large quantities and in a short time. As one of the most automated and mechanized agricultural sectors it contains significant potential to meet the needs of the country's food resources. Poultry production has several advantages compared to pigs and cattle, namely for maturation compared to other animal products, half the consumption power in 3-5 times lower in feed use of protein. Despite the fact that the domestic industrial poultry farming is gradually emerging in the general stabilization but significant rise is observed. A number of major theoretical and practical issues of commercial poultry and problems to improve its efficiency are not studied enough or need to be reviewed from the standpoint of modernity, particularly in the context of Ukraine's accession to the WTO. The authors reviewed the scientific and practical principles and current status of poultry and efficiency cost of its products in agricultural enterprises. It is necessary to investigate the problems and prospects of functioning of the industry. The analysis of poultry production by categories of farms in Ukraine was made. The basic directions and practical principles enhance the economic efficiency of poultry farming in Ukraine.